A bizalom és a társaság kapcsolata és annak hatása a döntéshozatalra - Lazányi, Kornélia (Közép-Európai Közlemények, 2017)
Social embeddedness, and the perceived level of social support are essential elements of the decision making. They influence the individual’s choices and decisions in a number of ways. One of them is via trust, and its effect on decisions. Hence, present paper tackles the topic of trust from the aspect of uncertainty and decisions made under uncertain conditions, where trust and social embeddedness are crucial factors of the equation. The aim is not only to present relevant international literature of the topic, but to investigate the actual and factual relation of these variables. Hence a research on a sample of 269 university students have been made to explore the effect social embeddedness has on the perceived level of social support and the students’ behaviour regarding uncertainty and trust.